2010
DOI: 10.1159/000319151
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Nicotine on Lipopolysaccharide-Induced Acute Lung Injury in Mice

Abstract: Background: Recently, nicotine administration has been shown to be a potent inhibitor of a variety of innate immune responses, including endotoxin-induced sepsis. Objective: It was the aim of this study to evaluate the effect of nicotine on attenuating lung injury and improving the survival in mice with lipopolysaccharide (LPS)-induced acute lung injury (ALI). Methods: ALI was induced in mice by intratracheal instillation of LPS (3 mg/ml). The mice received intratracheal instillation of nicotine (50, 250 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 46 publications
(35 reference statements)
4
15
0
Order By: Relevance
“…In the present study, the effect of tanshinone II on ALI in an LPS-induced lung injury rat model was analyzed. Administration of LPS induces cellular inflammatory processes and subsequent pulmonary injury in animals (22,23). The present results demonstrated that LPS administration enhanced the concentration of proteins in pulmonary fluid of rats.…”
Section: Discussionsupporting
confidence: 62%
“…In the present study, the effect of tanshinone II on ALI in an LPS-induced lung injury rat model was analyzed. Administration of LPS induces cellular inflammatory processes and subsequent pulmonary injury in animals (22,23). The present results demonstrated that LPS administration enhanced the concentration of proteins in pulmonary fluid of rats.…”
Section: Discussionsupporting
confidence: 62%
“…LPS is a principal component of the outer membrane of Gram-negative bacteria and can enter the blood stream and elicit inflammatory responses that may lead to shock and ultimately to death (20). LPS-induced lung injury in the rat is frequently used as a model for studying ALI (21). Thus, this model was used in the present study to investigate the prevention of AAP on LPS-induced ALI in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, nicotine improved survival in septic animal models, even if nicotine was given after the onset of sepsis [10] . The paper by Ni et al [11] in this issue of Respiration confirmed this sentinel observation, supporting the concept that targeting the 'late-phase' inflammatory response opens up novel options for the management of ALI. They showed reduced lung damage, neutrophil recruitment into the lung, cytokine production and survival even if the nicotine was given 24 h after the injurious insult.…”
mentioning
confidence: 57%
“…A key issue is whether the inciting trigger for ALI determines the response to blocking ␣ 7nAChR, highlighted by the contrasting results from the instilling lipopolysaccharide in the lung [10,11] to ALI induced by the systemic effects of the remote infection [14] . In general, ALI induced by triggers such as trauma and acid aspiration has better outcomes than ALI triggered by systemic infection or sepsis.…”
mentioning
confidence: 99%